Performance of production engineering students in enade: a statistical analysis of ethno-racial and gender diversity - Souza, Alex Fernandes de; Verri, Filipe Alves Neto; Balestrassi, Pedro Paulo (Brazilian Journal of Production Engineering, 2024)
Educational equity is crucial for social and economic development. This study aimed to conduct an ethnic-racial and gender statistical analysis of student performance in the ENADE for the Production Engineering course, considering data from the years 2014, 2017, and 2019. The methodology involved collecting data from INEP, including demographic and academic variables. After cleaning and filtering the data to include only students with confirmed attendance in ENADE, descriptive statistics were calculated by year and ethnic-racial and gender categories. To investigate significant differences in performance between groups, descriptive statistics and an analysis of variance (ANOVA) were used. Additionally, a linear regression was performed within the established racial framework to predict student performance based on demographic and academic characteristics, assessing the efficiency of the predictive model. The results showed significant disparities in academic performance between different races and genders, suggesting inequalities in access to educational resources and experiences of discrimination. These findings underscore the need for more inclusive educational policies to promote equity in higher education.
Keywords: Educational Equity; Racial Inequality; Statistical Analysis